In Vitro Cytotoxicity Test Reveals Non-toxic of Waste-based Scaffold on Human Hepatocyte Cells - Oktantia Frenny Anggani; Aniek Setiya Budiatin; Laksmi Sulmartiwi; Muhammad Rahmad Royan (Department of Aquaculture, 2021)
Scaffold, as one of the components for bone tissue engineering, requires formulated biomaterials that are both structurally and compositively similar to bone composition. Among others, chitosan, gelatin and chondroitin sulfate are known as potential candidates for scaffold composites that can be easily obtained from waste-based resources. This study aims to investigate the cytotoxicity of different scaffold composition and concentration regimes derived from waste-based chitosan, gelatine and chondroitin sulfate, in vitro. The composition regimes used were (Chitosan : Gelatin : Chondroitin Sulfate) 50 : 50 : 0 (A); 50 : 40 :10 (B); 50 : 35 : 15 (C); 50 : 30 : 20 (D); 50 : 25 : 25 (E). Meanwhile, the final concentrations of scaffold used were 2000, 1000, 500, 250, 100, 10 and 0,1 mg/ml. The different compositions and concentrations of scaffold was tested against Hepatocellular Carcinoma (Huh7it / Human Hepatocyte It). After 48-hour incubation in the scaffold solution, the percentage of cell viability was evaluated using 3-(4,5-dimethylthiazol-2yl)-5(3-carboxymethoxyphenyl)-2- (4-sulfophenyl)-2H-tetrazolium (MTT) assay. The result shows that there is no difference observed among different scaffold compositions on the cell viability (p > 0.05). However, different concentrations of scaffold show significant differences in cell viability in composition C and E (p < 0.01), suggesting possible dose- dependent effect of scaffold on cell viability. Overall, all the waste-based scaffold compositions show no toxicity against the Hepatocellular Carcinoma cells as exhibited by the cell viability that is above 70%, at least with the concentration up to 2000 mg/ml.